Amino acid metabolism in primary bone sarcomas - Jiménez, Jennifer A.; Lawlor, Elizabeth R.; Lyssiotis, Costas A. (Frontiers in Oncology, 2022)
Primary bone sarcomas, including osteosarcoma (OS) and Ewing sarcoma (ES), are aggressive tumors with peak incidence in childhood and adolescence. The intense standard treatment for these patients consists of combined surgery and/or radiation and maximal doses of chemotherapy; a regimen that has not seen improvement in decades. Like other tumor types, ES and OS are characterized by dysregulated cellular metabolism and a rewiring of metabolic pathways to support the biosynthetic demands of malignant growth. Not only are cancer cells characterized by Warburg metabolism, or aerobic glycolysis, but emerging work has revealed a dependence on amino acid metabolism. Aside from incorporation into proteins, amino acids serve critical functions in redox balance, energy homeostasis, and epigenetic maintenance. In this review, we summarize current studies describing the amino acid metabolic requirements of primary bone sarcomas, focusing on OS and ES, and compare these dependencies in the normal bone and malignant tumor contexts. We also examine insights that can be gleaned from other cancers to better understand differential metabolic susceptibilities between primary and metastatic tumor microenvironments. Lastly, we discuss potential metabolic vulnerabilities that may be exploited therapeutically and provide better-targeted treatments to improve the current standard of care.